How to regulate Information and Communications Technology?: A jurisprudential inquiry into legislative and regulatory techniques - Ubena, John (Stockholm University, 2023)
ICT transformations digitalisation, computerisation and distributed networks have enabled emergence of new goods, services and applications that have changed the way behaviours are conducted. Moreover, ICT goods have been transformed into services, blurring established legal categories. ICT transformations have also brought conflicts of interests and imbalances of new kinds. In other cases fundamental rights have been threatened. Use of traditional legislative techniques (TLTs) based on command and control regulation has often resulted in banning certain applications or criminalising behaviours. But such an approach risks stifling innovation, and expanding the imbalances. TLTs frequently also face practical ineffectiveness. To address the problem, emerged a New Regulatory Culture (NRC), reflecting a number of complementary regulatory approaches, e.g. strategies based on freedom of contract, technical measures of protection, proactive means based on economic incentives, disclosures, and a shift from behaviour norms to duty of care norms. This study explores shortcomings of the TLTs and draws the potentialities and risks of the NRC approaches in ICT regulation. The criteria for assessing the approaches include functional effectiveness and the ability to uphold the Rule of Law and fundamental rights. Three problem areas in ICT law are analysed: digital copyright, Voice over Internet Protocol and net neutrality. It is concluded that the understanding of shortcomings of TLTs regime, its development into NRC as well as grasping the NRC’s potentialities and risks in ICT regulation is beneficial. Such broader understanding may help to identify ICT regulatory problems parallel with improving the regulatory framework and enable regulation to steer technology transformations without compromising other interests. This is important because the different types of NRC approaches may be suitable for diverse ICT regulatory problems and regulatory purposes.